Peluang Pengusaha Mikro dan Kecil (UMK) Menggunakan Layanan Digital Lembaga Keuangan Mikro Syariah - Lubis, Chairia; Nugroho, Lucky; Fitrijanti, Tettet; Sukmadilaga, Citra (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2020)
The purpose of this study was to find out the opportunities of digital services owned by Sharia Micro Finance Institutions (Baitul Mal Wa Tamwil-BMT) to reach Micro and Small (MSME) customers. Therefore the research question in this article is how the opportunities for the use of digital services by MSEs. This research method uses library research and interviews with BMT managers so that this research is qualitative. Following the results of the study, BMTs must collaborate with financial technology (fintech) companies to provide customer application. Furthermore,